2012
DOI: 10.1111/j.1469-0691.2011.03655.x
|View full text |Cite
|
Sign up to set email alerts
|

Oropharyngeal yeast colonization in HIV-infected outpatients in southern Taiwan: CD4 count, efavirenz therapy and intravenous drug use matter

Abstract: To understand the status of oropharyngeal yeast colonization in human immunodeficiency virus (HIV) -infected outpatients in the era of highly active antiretroviral therapy (HAART), we conducted a prospective, cross-sectional study from October 2009 to January 2010 at a medical centre in southern Taiwan. Fungal cultures of the oropharyngeal swabs were performed on 327 enrolled patients. At enrolment, 258 (79%) patients had been receiving HAART, and 42 (12.8%), 73 (22.3%) and 212 (64.8%) patients had CD4 cell co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
34
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 23 publications
8
34
0
2
Order By: Relevance
“…The effect of highly active ART on the risk of Candida colonization in HIV-infected has been described elsewhere. While a slight decrease [34] or no effect [5,10] on oropharyngeal yeast colonization in patients receiving ART has been reported, other authors also observed a protective effect of ART treatment regimens [7,11]. On the other hand, higher oropharyngeal Candida carriage has been detected in ART-treated HIVinfected individuals [2].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The effect of highly active ART on the risk of Candida colonization in HIV-infected has been described elsewhere. While a slight decrease [34] or no effect [5,10] on oropharyngeal yeast colonization in patients receiving ART has been reported, other authors also observed a protective effect of ART treatment regimens [7,11]. On the other hand, higher oropharyngeal Candida carriage has been detected in ART-treated HIVinfected individuals [2].…”
Section: Discussionmentioning
confidence: 94%
“…In individuals infected with human immunodeficiency virus (HIV), the prevalence of asymptomatic colonization of oral mucous is higher, approaching 80% [3][4][5][6][7][8][9][10][11]. Importantly, colonization of skin and mucous membranes with Candida species is an important risk factor that predisposes to candidiasis [12], whose clinical manifestations range from mucosal to life-threatening disseminated infections.…”
Section: Introductionmentioning
confidence: 99%
“…In Taiwan, the number of HIV-infected patients receiving highly active antiretroviral therapy (HAART) with a favorable CD4 count and suppressed viral load has increased in the recent decade due to the availability of free HAART and implementation of a case management program [8]. Since 1999, the authors have examined the prevalence of and risk factors for oral Candida colonization among HIV-infected outpatients at three hospitals during 2009–2010 in three studies [911]. …”
Section: Introductionmentioning
confidence: 99%
“…Taken together, these epidemiological changes suggested the need for reevaluating the prevalence of and risk factors for MRSA carriage among the contemporary HIV-infected population. Here, the same study population from 2009–2010 [911] was enrolled to investigate (1) the prevalence of and risk factors for nasal and oral S. aureus and MRSA colonization in order to compare with those for oral Candida colonization, and (2) the microbiologic characteristics and clonality of the MRSA colonizing strains. The study results could be helpful for targeted MRSA screening and transmission prevention in this population and expanding our knowledge about the interplay between S. aureus and Candida species in the oral cavity.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that Candida could be isolated in the oral cavity of 15.2 to 75 % of healthy individuals [2,3]. The difference in population characteristics, sampling approach, and geographic area might contribute to the diversity of detection rates [4][5][6]. When appropriate conditions such as local or systemic deficiencies in the host defenses exist, they multiply, even causing multiple infections [7].…”
Section: Introductionmentioning
confidence: 99%